Parental Guidance Suggested: Engaging Parents as Partners in Research Studies of Genomic Screening for a Pediatric Population - Powell, Sabrina N.; Byfield, Grace; Bennetone, Ashley; Frantz, Annabelle M.; Harrison, Langston K.; James-Crook, Erin R.; Osborne, Heather; Owens, Thomas H.; Shaw, Jonathan L.; O’Daniel, Julianne; Milko, Laura V. (Frontiers in Genetics, 2022)
Recent advances in genomic sequencing and genomic medicine are reshaping the landscape of clinical care. As a screening modality, genetic sequencing has the potential to dramatically expand the clinical utility of newborn screening (NBS), though significant barriers remain regarding ethical, legal, and social implications (ELSI) and technical and evidentiary challenges. Stakeholder-informed implementation research is poised to grapple with many of these barriers, and parents are crucial stakeholders in this process. We describe the formation and activities of a Community Research Board (CRB) composed of parents with diverse backgrounds assembled to participate in an ongoing research partnership with genomic and public health researchers at the University of North Carolina. The mission of the CRB is to provide insight into parental perspectives regarding the prospect of adding genomic sequencing to NBS and collaboratively develop strategies to ensure its equitable uptake. We describe how these contributions can improve the accessibility of research and recruitment methods and promote trust and inclusivity within diverse communities to maximize the societal benefit of population genomic screening in healthy children.